2010
DOI: 10.1111/j.1365-2427.2009.02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of grazing impacts of an algivorous fish (Pseudogastromyzon myersi: Balitoridae) to seasonal disturbance in Hong Kong streams

Abstract: 1. Manipulative experiments were carried out in four Hong Kong streams (two shaded, two unshaded) to investigate the impact of grazing by an algivorous fish, Pseudogastromyzon myersi, on benthic algal biomass and assemblage composition. Experiments were conducted and repeated during both the dry and wet seasons to determine whether spate-induced disturbance modified any grazing effect. Treatments comprised fish exclusion and inclusion via closed and open cages, with a no-cage treatment used as a control for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 50 publications
(156 reference statements)
2
23
0
Order By: Relevance
“…Significantly, also found that breakdown rates of L. formosana were positively related to densities of benthic shredders during the dry season in eight Hong Kong streams (four shaded, four unshaded). The seasonal shift from determination of litter breakdown rates by flow volume during the high-discharge period (wet season) to a weaker dependence on flow under base-flow conditions (dry season) when biotic processes were more discernable is mirrored by studies of algal grazing in four unregulated Hong Kong streams where the influence of herbivorous fish detected during the dry season was overwhelmed by spate-induced disturbance during the wet season (Yang & Dudgeon, 2010). It is conceivable that under high-flow conditions during the wet season, flow may fragment leaves so rapidly that it is the only determinant of breakdown rate.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, also found that breakdown rates of L. formosana were positively related to densities of benthic shredders during the dry season in eight Hong Kong streams (four shaded, four unshaded). The seasonal shift from determination of litter breakdown rates by flow volume during the high-discharge period (wet season) to a weaker dependence on flow under base-flow conditions (dry season) when biotic processes were more discernable is mirrored by studies of algal grazing in four unregulated Hong Kong streams where the influence of herbivorous fish detected during the dry season was overwhelmed by spate-induced disturbance during the wet season (Yang & Dudgeon, 2010). It is conceivable that under high-flow conditions during the wet season, flow may fragment leaves so rapidly that it is the only determinant of breakdown rate.…”
Section: Discussionmentioning
confidence: 99%
“…These 'flashy flows' scour out habitats, physically removing taxa, and therefore may be more important in structuring macroinvertebrates than the presence of shrimp or fish (Bond & Downes, 2000). The hypothesis that predation and competition are less important in highly disturbed streams and rivers has been suggested for systems in other parts of the world (Bishop, 1973;Peckarsky et al, 1990;Yang & Dudgeon, 2010). Flash floods can create relatively unpredictable systems (Boulton et al, 2008) characterized by a continuum of conditions that may ultimately result in two distinct environments occurring at various times within a given portion of a stream.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs against a background of seasonal variation in epibenthic algal assemblages in stream reaches that do not experience water extractions. These may be induced by flow (Yang et al, 2009) as well as top-down control of biomass and composition by grazing fish (Yang & Dudgeon, 2010b). In this study, we compared epibenthic algal assemblages between upand down-stream reaches of a number of streams experiencing varying degrees of water abstraction.…”
Section: Introductionmentioning
confidence: 99%